The Performance of Two Species of Black Cumin (Nigella sativa L.) and (Nigella arvensis L.) Under Different Sowing Dates in Spring and Autumn at hallabja Governorate /Iraqi Kurdistan Region. - A. Al-Zubaidy, Adel M.; S.Ghafoor, Bakhtiar; Rasul, Abdulsalam A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
Two field experiments were performed to study the response of two species , Nigella sativa L. and Nigella arvensis L. within different sowing dates at spring and autumn seasons which included 1st and 20th March, 10th April and 1st May for spring season, while the sowing dates for the autumn season were, 2nd November, 21st November, 11th December, 31stDecember and 20thJanuary. Both experiments conducted according to the Completely Randomized Block Design (CRBD) within three replications at hallabja/Kurdistan Region, located [35Â°12'48.7"N; 45Â°57'34.4"E] and the altitude was 596 masl. Results showed that among the four different sowing dates of spring cultivations,  both species were responded to only 1st and 20th March date with some superiority of the 1st March, otherwise the survival and their yield were not acceptable at sowing date later than 20th March, while at the autumn cultivation, both species responded to all sowing date, but not to be later than 31st December, the early dates 2nd November and 21st November were showed significant differences in most yield traits. The result of the study showed that, due to the favorable environmental condition and the longer period of growth at autumn cultivation, most of the yield traits were gained significant values as the average of both species and different sowing dates of autumn compared to that occurred at spring cultivations. Some chemical contents of both species under the different environment conditions showed significant differences. Generally, N. sativa compared to N. arvensis contained more significant chemical compounds in the term of carbohydrates and protein at autumn, fixed and volatile oils at spring.